Enhancing security for end users in cloud computing environment using hybrid encryption technique - R.K, Nadesh; R, Srinivasa Perumal; P.G, Shynu; Sharma, Gaurav (International Journal of Engineering and Technology, 2018)
In the era of cloud, anything and everything as a service facilitates number of remote user connected from anywhere, anytime and any form of access to the storage services. Today, Cloud storage has become an essential aspect of cloud computing, stores information and support any kind of applications. Applications like Internet of Things, Big Data analytics, Data warehousing, Databases, Backups and archive applications all rely on some form or the other on cloud storage architecture. Users may have a different variants of smart devices such as tablet, PCs, notebook and smart phones. Cloud storage provides an interlink between these smart devices. Enterprises prefer to use cloud storage because they provide cost-friendly and flexible alternatives on locally implemented hardware. However, business process in the cloud needs secured transaction, confidential files are sometimes exposed to risk of leakage, as cloud- stored data resides outside of the local infrastructure, thus vulnerable to security risks. Cloud storage providers provides enough security at their end, but there is no system that provides client level security while using public clouds. The proposed system will provide client level security using hybrid encryption techniques. Using AES (Advance Encryption Standard) in CBC Mode (Cipher Block Chaining) and HMAC-SHA-1 (Hash-based Message Authentication Code) with light weight methods enhances the strong encryption at client level security. Fusion of these algorithms adds extra layers of security to the cloud storage data. The proposed method enhances the security measures for any client users, using storage as a service offered by several cloud service providers.
Keywords: Authentication; Cipher Block Chaining; Cloud Security; Cloud Storage; Encryption